THE ECONOMIC CAPACITY INCREASING OF FARMERS' HOUSEHOLDS THROUGH THE BUSINESS PROSPECTS PROGRAM OF ORNAMENTAL PLANTS AND FERTILIZER BOKASHI PLUS IN GAMPONG REULEUT TIMU, MUARA BATU DISTRICT, NORTH ACEH. - Tambarta, Emmia; Mawardati; Jamilah; Muliana (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2022)
Agriculture Faculty of UNIMAL is one of the leading faculties in the field of agriculture and fisheries development in Sumatra. The idea of ​​introducing ornamental plant business prospects was based on the COVID-19 pandemic, which dealt a tremendous blow to the economy of the community around the UNIMAL Faculty of Agriculture. The majority of the people around the institution have house rentals for UNIMAL students. The COVID-19 pandemic condition in Aceh forced UNIMAL to change the offline education system to an online system according to the direction of the Ministry of Education and Culture. This is done to prevent the spread of the COVID-19 virus. In the online system, students carry out the learning process from their home region so they are not in the environment around UNIMAL. This has a direct impact on the people of East Reulet as a provider of rental houses. The solution that the team recommends is to turn into small and medium entrepreneurs who can generate additional income. The group of mothers can take advantage of their hobby, namely planting and collecting ornamental plants into an ornamental plant business that has great opportunities to be developed. The next solution is that housewives around Reulet Timur can use agricultural waste around them to be processed into bokashi plus fertilizer. Agricultural waste can damage the nutrient balance of the soil and invite pests and diseases in the surrounding area. The location of this activity is in Reuleut Timur Village, Muara Batu District, North Aceh Luaran Regency which is produced in the form of OJS-based service journals, online publications in mass media, and ornamental plant products and bokashi plus fertilizer which are ready to be marketed. The outputs of this service are articles in the IRPITAGE service journal Vol 1 (2) December 2021, news on activities on the fp.unimal.ac.id website, SPK (Cooperation Agreement) with partners and ornamental plant and fertilizer products.